Low energy repair of co-continuous metal-ceramic composites using electrodeposition. (February 2023) - Mahmoudi, Mohammadreza; Oh, Se; Minary-Jolandan, Majid
The concept of self-healing materials, mainly inspired from biological systems, in the last several decades has been pursued toward fully autonomous materials and structures. Self-healing of polymers (extensively) and metals (to much less extent) have been demonstrated, however, there are no such reports for metal-ceramic composites. Metal-ceramic composites are technologically significant as structural and functional materials and are among the most expensive materials to manufacture and repair. Hence, technologies for self-healing metal-ceramic composites are of paramount importance. Here, we demonstrate a concept to fabricate and heal co-continuous metal-ceramic composites at room temperature. The composites are fabricated by infiltration of metal (here copper) into a porous alumina preform (fabricated by freeze-casting) through electroplating; a low-temperature and low-cost (by ∼60-times lower cost compared to traditional molten metal infiltration) process for fabrication of such composites. Additionally, the same electroplating process is demonstrated for healing damages such as grooves and cracks in the original composite, such that the healed composite recovers its strength by more than 80%. Such technology may be expanded toward fully autonomous self-healing structures.